Structural and Optical Properties of Vacuum Coated and Annealed Copper Phthalocyanine (CUPC) Thin Films. (2015) - Vidya, C.; Hoskeri, Priya A.; Joseph, C.M.
Abstract: Heat treatment is able to cause the structural transformation of phthalocyanine thin film during the post-deposition heat treatment. The annealing effects of the process on the film characteristics of vacuum deposited copper phthalocyanine thin films were studied. However, the pre-annealing leads to a larger-grain and a more compact structure. Structure transformation was inhibited by post-deposition annealing at 300oC. Thin films of CuPc were deposited using vacuum evaporation technique method onto glass substrates. The films were annealed at 4 different temperatures (323, 333, 343 and 353 K) in air at different intervals of time. Optical studies were done and the results are discussed. The optical band gap for the film as obtained from the graph for all the thin films are tabulated and analyzed. X ray diffraction studies on the deposited film showed crystallinity with a major peak for CuPc.